PENGARUH TEPUNG KUNYIT (Curcuma longa L.) TERHADAP KADAR KOLESTEROL DAN KADAR TRIGLISERIDA DARAH BURUNG PUYUH (Coturnix coturnix japonica L.) - Sheila Widowati; Koen Praseno; Tyas Rini Saraswati (Jurnal Akademika Biologi, 2012)
This study aims to determine the potential of turmeric powder to the vitality of the quail with blood cholesterol and triglyceride levels. Results of studies using different concentrations of turmeric powder. One set of experiments consisted of 4 treatments each consisting of three tail quail and performed five repetitions. Given concentration is 0 mg / head / day; 13'5 mg / head / day; 27 mg / head / day; 54 mg / head / day for increased vitality through the levels of cholesterol and triglycerides. Data were analyzed using ANOVA (analysis of varian). Analysis showed significantly different levels of cholesterol and triglycerides in the blood. Provision of turmeric powder (Curcuma longa L.) in this study has the potential to lower cholesterol and blood triglycerides quail.Keyword : cholesterol and triglycerides, quail (Coturnix coturnix japonica L.), turmeric powder